USING GUESS THE WORD GAME IN ENHANCING THE SPEAKING ABILITY OF SEVENTH GRADE STUDENTS AT STATE JUNIOR HIGH SCHOOL NUMBER 30 PALEMBANG - Mahfi Putra Riansyah; Asti Veto Mortini; Marleni (Esteem Journal of English Education Study Programme, 2024)
This research investigates the impact of the Guess the Word Game on improving the speaking proficiency of seventh-grade students at Junior High School 30. Palembang employed a singular class in an experimental design. The class utilized the Guess the Word game as the principal instructional method to enhance students' speaking abilities. Pre-test and post-test evaluations were administered to examine the pupils' advancement in speaking proficiency. The results indicated a significant enhancement in students' speaking skills following their participation in the game, demonstrating that the inclusion of interactive activities such as the Guess the Word Game can serve as an effective approach for improving student engagement and language competency. This study indicates that game-based learning may serve as an innovative approach to enhance speaking skills in educational environments.